Kemampuan Berpikir Kreatif Matematika pada Siswa Bergaya Belajar Visual - Astuti Astuti; Syahfitriani Br Ginting; Paustina Ngali Mahuze; Serlina Boru Sinaga; Rival Hanip; Najdah Thalib; Prima Lestari Situmorang (CV. Alim's Publishing, 2024)
Creative thinking skills emphasize ways of thinking so that students are able to face problems in the future. One of the subjects that can develop creative thinking skills is mathematics. Each student has their own way of learning mathematics, such as looking at diagrams. The ability to obtain information relying on the sense of sight is known as the visual learning style. The research aims to analyze thinking abilities in 3 categories, namely high, medium and low in visual learning style students. The research was conducted on 35 class IVA students with 3 research subjects representing each category of creative thinking ability. The results of the research show that students with a visual learning style with high creative thinking meet 3 of the 4 indicators, while students with a moderate creative thinking style, especially with a visual learning style, do not meet the indicators of creative thinking ability due to lack of accuracy in calculations, while students with a visual learning style with low creative ability do not meet all the thinking indicators. creative because they have not been able to take steps to solve it so the calculations are not correct.